The televisión: A way to educate (Journal of Parents and Teachers, 2023)
This article talks about the huge influence of the television in the life of nowadays kids. At the beginning it criticizes some aspects of them but then it gives us some tips about the benefits that we can obtain and the appropriate programs to educate. It also compares it with the reading.
Keywords: television; educate; reading